Sexual dysfunction and divorce in Iran: A systematic review - Fatemeh Daneshfar; Afsaneh Keramat (Journal of Family Medicine and Primary Care, 2023)
Introduction: One of the causes of dissatisfaction between couples is sexual dysfunction that sometimes leads to divorce. The present systematic study was conducted to evaluate the factors affecting sexual dysfunction and divorce in Iran. Method: A comprehensive search, including keywords of sexual dysfunction, emotional divorce, breakaway, separation, conflict, and Iran, was conducted on the databases of Scopus, MEDLINE/PubMed, CINAHL, Web of Science, Magiran, IranMedex, and SID. Out of the total number of reviewed articles, 16 articles met the inclusion criteria. No time limit was considered for our research and all published articles up to November 2021 were reviewed. Results: Based on the results of the present study, in all of the reviewed articles, sexual problems and dissatisfaction were among the effective factors in the occurrence or request of a formal divorce or an emotional divorce. The data also demonstrated that weakness in arousal and sexual desire, weakness in sexual function, sexual disorders, orgasm problems, and pain were among the problems of people on the verge of divorce. Conclusion: Due to the importance of this issue, recognizing the effective and influential factors of divorce is one of the priorities of mental health. Dissatisfaction with sexual relations in both or one of the spouses is found to be one of the most important factors involved in divorce. If there are problems such as sexual dysfunction between the couples, they may still live together due to cultural and social conditions; however, they may experience emotional divorce. Therefore, there is an urgent need for effective counseling and treatment programs in this regard.